2011
DOI: 10.1111/j.1467-789x.2011.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity and hypoferraemia in adults: a systematic review

Abstract: A growing number of studies suggest a potential link between obesity and altered iron metabolism. The purpose of this systematic review was to examine existing literature on iron status in obese populations. A comprehensive literature search was conducted. Included studies recruited participants ≥ 18 years with a body mass index ≥ 30 kg m(-2) and provided descriptive statistics for haemoglobin or ferritin at a minimum. There were 25 studies meeting all eligibility criteria, of these 10 examined iron status in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 62 publications
4
98
0
7
Order By: Relevance
“…In other words, a high level of serum ferritin represents a high level of iron accumulation in healthy individuals. However, some reports have shown that obesity is associated with iron deficiency [16][17][18]. Thus, the exact nature of the relationship between serum ferritin level and obesity remains unclear.…”
Section: Clinical and Laboratory Measurementsmentioning
confidence: 99%
“…In other words, a high level of serum ferritin represents a high level of iron accumulation in healthy individuals. However, some reports have shown that obesity is associated with iron deficiency [16][17][18]. Thus, the exact nature of the relationship between serum ferritin level and obesity remains unclear.…”
Section: Clinical and Laboratory Measurementsmentioning
confidence: 99%
“…Initially, iron deficiency in a population of obese people was linked to a low level of physical activity, poor dietary habits, and increased requirement of iron related to larger blood volume and obesity. Recently, depleted iron stores in obese subjects were linked to inflammation and hepcidin influence on iron influx into plasma through its down-regulating action on ferroportin-1 [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Before surgery (at baseline), systemic lowgrade inflammation influenced the increase of ferritin levels; however, before and after surgery, ferritin values were determined by serum iron levels, iron intake, and hepcidin. In obesity, increased ferritin levels are associated with low transferrin saturation and hypoferremia, but those with obesity do not seem to be more prone to anemia, compared to eutrophic subjects (25,38). Most of these changes are related to the anemia of inflammation, in which mechanisms are stimulated by proinflammatory cytokines and hepcidin (16).…”
Section: Discussionmentioning
confidence: 99%
“…The minerals presented in the formula were chelated into an amino acid (glycine). The micronutrient supplementation of 2 RDAs (26) was suggested to be given daily for RYGB surgery in two doses (11,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Adequate Intake (AI) (26) was used when the RDA was not established for the micronutrient (except for calcium).…”
Section: Micronutrient Supplementationmentioning
confidence: 99%
See 1 more Smart Citation